Effect of Liquidity, Asset Management, Leverage and Dividend Policy on Firm Value at Food and Beverages Companies Listed on the Indonesia Stock Exchange - Andreas Andreas; Christin Christin; Shelly Wijaya Wijaya; Jessi Charina Sembiring (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to analyze the effect of liquidity, asset management, leverage and dividend policy on firm value at Food and Beverages Companies listed on the Indonesia Stock Exchange. The type of research used is quantitative research because the data used is numbers while the nature of this research is descriptive research. The population in this study amounted to 30 Food and Beverages Companies listed on the Indonesia Stock Exchange. The research sample used is in the form of financial statements of Food and Beverages Companies listed on the Indonesia Stock Exchange with a total of 20 companies from 2016-2019. The results of this study indicate that the current ratio, total asset turnover, debt to equity ratio and dividend payout ratio have a positive and significant effect on firm value at Food and Beverages Companies